Implementation of fault tree analysis to a prototype of employee leave information system - Eko Yulianto; Siti Anisah; Taufik Asra; Irwan Agus Sobari (Institute of Computer Science (IOCS), 2023)
The problem faced by companies in general is the delay in agreeing to apply for leave, this is caused by two things, namely too many stages to be skipped and the difficulty of meeting with the boss whenever he wants to apply for leave. The purpose of this research is to design a proposed design for a leave application information system. The development method used is the prorotype method, while the method used to find the root of the problem is one of the techniques in Root Cause Analysis, namely Fault Tree Analysis. The results of this study are a prototype proposal that can be taken into consideration for companies to start implementing a digital-based system for submitting employee leave. The results of this study are expected to provide information as a basis for consideration, support, and contributions to ideas for companies to be able to use technology in the process of applying for employee leave